Bridging the Break: Three Approaches to Root Fracture Management Using Bioactive Glass Material, Fiber Post, and Orthodontic Stabilization: A Case Series - Bathla, Saurav; Dutta, Saurav Kumar; Borah, Dolma; Singh, Tanu (Iranian Endodontic Journal, 2026)
Dental trauma is a common clinical presentation and may involve injury to the crown, root, or supporting periodontal tissues. Horizontal root fractures affect dentin, cementum, and the pulp and present significant diagnostic and therapeutic challenges. Inappropriate or delayed management may lead to pulp necrosis, internal or external root resorption, displacement of the affected tooth, and loss of functional arch continuity. The management of horizontal radicular fractures is often complex and frequently requires a multidisciplinary approach involving endodontic, periodontal, prosthodontic, and orthodontic procedures to achieve adequate stabilization and healing. This case series reports three cases of horizontal root fractures, each managed using a different treatment modality, including a bioactive glass–based sealer in putty consistency, fiberglass post reinforcement, and orthodontic wire stabilization. The treatment approach in each case was selected based on fracture location, degree of mobility, and overall clinical presentation. Early diagnosis combined with an individualized and well-planned treatment strategy can enhance healing and preserve the affected tooth. These cases emphasize the importance of case-specific management in achieving favorable and predictable clinical outcomes.